The Influence of the Digital Era on the Strengthening of Religious and Cultural Literacy Values among Students of the Study of Religions Program - Desi Ramdani; Husna Amin; Nofal Liata (Muqaranah Al-Adyan: Multidisciplinary Perspective on Religions, 2025)
The digital era has significantly influenced students’ ways of thinking, behavior, and value systems, including those related to religious and cultural literacy. This study aims to analyze the influence of the digital era on the strengthening of religious and cultural literacy values among students of the Study of Religions Program. This research employs a qualitative descriptive approach, with data collected through interviews, observation, and documentation. The findings indicate that the digital era provides easier access to religious and cultural information while also posing challenges in preserving authenticity and religious identity. Positive use of digital technology can enhance interreligious understanding and cultural awareness, whereas uncontrolled use may lead to value disorientation. Therefore, an integrated digital literacy strategy within religious and cultural education is essential to help students critically select information and maintain religious values as well as local cultural wisdom amid digital globalization.